Leaf structure and histochemical investigation in Papaver Rhoeas L. (Corn poppy, field poppy) - Christodoulakis, N.S.; Tsiarta, M.; Fasseas, C. (Journal of Herbs, Spices and Medicinal Plants, 2013)
The anatomy of the dorsiventral, amphistomatic leaf of Papaver rhoeas was investigated. It was a simple structure possessing large epidermal cells having their vacuole impregnated with glycoproteins which varied in texture, forming a dense, hard core in the middle of the vacuole. Slender rays of cisternae radiated from the dense central core to the cell wall. Thin-walled palisade cells presented a unique, lobed shape probably creating larger surfaces for gas exchange. Mesophyll cells secreted phenolics, condensed tannins, alkaloids, terpene containing steroids and sesquiterpenes. P. rhoeas although being a therophyte, has adopted some structural features common in mediterranean phanerophytes. © 2013 Taylor & Francis Group, LLC.
Keywords: alkaloid; article; cell vacuole; cell wall; chloroplast; controlled study; dicotyledon; epidermis cell; gas exchange; glycoprotein; Histochemistry; histology; leaf; Leaf anatomy; leaf gas exchange; leaf morphology; leaf structure; mesophyll cell; nonhuman; palisade parenchyma; Papaver; papaver rhoeas; phenol; phytochemistry; plant stoma; Protein; secondary metabolite; Secondary metabolites; Secreting activity; secretion; sesquiterpene; steroid; tannin; terpene